Influence of Pricing Factor Dimension on the Cadastral Cost of Urban Land Plot - PRAVDINA, Ekaterina Aleksandrovna; LEPIKHINA, Olga Jurjevna (Journal of Environmental Management and Tourism; Vol 7 No 3 (2016): JEMT Volume VII Issue 3(15) Fall 2016, 2016)
This article is dedicated to the analysis of dependence of urban land cadastral cost on pricing factors, where each factor’s influence can be expressed through the system of various pricing factors. The article reveals major factors influencing the cadastral cost of land plots, and proves that the influence of each of them could be expressed through the system of different estimated indicators. The article also provides options for such indicators with their statistical scales. The land fund of research objects – small and average cities of Murmansk region, is studied; lists of the estimated indicators of pricing factors are created. The digital maps of these cities containing layers of borders of the estimated land plots, objects of social, engineering, transport infrastructure and other data necessary for mass assessment were created by means of the geographic information system MAPINFO. Values of estimated indicators of factors are received. Several factor indicators showed weak degree of correlation dependence which testifies to impossibility of their interchangeability when forming statistical models. The influence of estimated indicator dimension on a type of statistical model of land cadastral cost is analyzed. Two test groups of different estimated factor indicators are created; the most significant indicators for each group are revealed using the method of correlation galaxies (by P.V. Terentiev). The statistical models of land cadastral cost calculation received on the basis of these indicators led to an essential difference in received costs of land plots which confirmed the hypothesis of the authors. Research results can be used when developing methodology support for mass cadastral assessment of urban lands in Russia.
Keywords: pricing factor; estimated indicator; mass assessment; cadastral cost; correlation galaxy method